Lymph node involvement in treatment-naïve prostate cancer patients: correlation of PSMA PET/CT imaging and roach formula in 280 men in radiotherapeutic management - Körber, Stefan A.; Kratochwil, Clemens; Häfner, Matthias; Rathke, Hendrik; Herfarth, Klaus; Holland-Letz, Tim; Haberkorn, Uwe; Debus, Jürgen; Giesel, Frederik L. (Journal of nuclear medicine, 2020)
The importance of prostate-specific membrane antigen (PSMA) PET/CT for primary staging of treatment-naïve prostate cancer patients is still under debate. Therefore, the present study aimed to evaluate the role of PSMA PET/CT in detecting nodal metastases in a large cohort of men and compare imaging results with the risk of lymph node involvement based on the Roach formula. Methods: In total, 280 men with newly diagnosed prostate carcinoma were included in the present study. For all patients, PSMA PET/CT was performed for primary staging. Median age was 67 y (range, 38-84 y), and 84% of all patients were classified as high-risk according to the d’Amico criteria. The risk of lymph node involvement was calculated using the Roach formula and compared with the PSMA PET/CT results. Results: PSMA-positive nodes were detected in 90 of 280 men (32.1%). Although most nodal metastases occurred within the pelvis, 36.0% were in extrapelvic sites. In 9 patients (3.2%), nodal metastases occurred in the Virchow node. After comparison of PSMA data with the results of the Roach formula, an area under the curve of 0.781 was obtained for the Roach predictions. Conclusion: For treatment-naïve prostate cancer patients, PSMA PET/CT is well suited for the detection of nodal metastases. However, the original Roach formula can still be used for a quick assessment of potential lymphatic spread in daily clinical routine.